2017
DOI: 10.11005/jbm.2017.24.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Current Role and Application of Teriparatide in Fracture Healing of Osteoporotic Patients: A Systematic Review

Abstract: BackgroundThe use of osteoanabolic agents to facilitate fracture healing has been of heightened interest to the field of orthopaedic trauma. This study aimed to evaluate the evidence of teriparatide for fracture healing and functional recovery in osteoporotic patients.MethodsWe performed a literature search in PubMed, EMBASE, Web of Science, and the Cochrane Library using terms including “Fracture” [tiab] AND “Teriparatide [tiab] OR “PTH” [tiab].ResultsThis systematic review included 6 randomized clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…[8][9][10] There has been previous reviews that suggest the role of TPTD as alternate to induce fracture healing. [11][12][13] However, to date, many clinical trials have been undertaken to elucidate the efficacy of TPTD for inducing fracture healing in several situations, such as atypical femoral fracture (AFF). [14][15][16] A better understanding of the role of TPTD with greater evidences on fractures healing could help clinician to make their decision.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] There has been previous reviews that suggest the role of TPTD as alternate to induce fracture healing. [11][12][13] However, to date, many clinical trials have been undertaken to elucidate the efficacy of TPTD for inducing fracture healing in several situations, such as atypical femoral fracture (AFF). [14][15][16] A better understanding of the role of TPTD with greater evidences on fractures healing could help clinician to make their decision.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that teriparatide yielded positive effects on radiographic bone healing in 6 studies, but was not associated with better radiographic outcome in 3 studies. They concluded that teriparatide provides selective advantages to fracture healing or functional recovery in management of osteoporotic fractures [13]. Bhandari et al performed a placebo-controlled phase 3 study to evaluate the effect of teriparatide on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatide, a parathyroid hormone (PTH) analogue, is a synthetic polypeptide hormone consisting of the 1–34 fragment of PTH, which is used in treatment of osteoporosis [12]. Recently, some reports have shown the ability of teriparatide to improve fracture healing [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Postmenopausal women with a distal radial fracture in need of closed reduction, but not surgery, were assigned to 8 weeks of teriparatide; the median time to complete cortical bridging was analyzed, and the time to heal was shorter than placebo. 13,14 We administered 20 mg teriparatide, injected subcutaneously during 6 weeks after performing rTSA in acute proximal humeral fractures. All patients in this group obtained tuberosity union.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that teriparatide, administered to the osteoporotic distal femur fracture, could accelerate initial callus formation, bridge callus formation, and consolidation. [13][14][15][16] From these cases, we evaluated the patient's range of motion and functional outcome. We found that there were significant differences between teriparatide and noteriparatide groups in external rotation (29.5 vs. 7.5 ; p ¼ 0.004), external rotation in 90 abduction (55 vs. 12.5 ; p < 0.020), forward flexion (120 vs. 105 ; p ¼ 0.002) range of motions, and ASES (84.5 vs. 74.6; p ¼ 0.019).…”
Section: Discussionmentioning
confidence: 99%